2010
DOI: 10.2340/16501977-0474
|View full text |Cite
|
Sign up to set email alerts
|

Goal attainment scaling in the evaluation of treatment of upper limb spasticity with botulinum toxin: A secondary analysis from a double-blind placebo-controlled randomized clinical trial

Abstract: Goal-attainment scaling provided a responsive measure for evaluating focal intervention for upper limb spasticity, identifying outcomes of importance to the individual/carers, not otherwise identifiable using standardized measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 27 publications
6
102
0
6
Order By: Relevance
“…Thus, our findings make a threefold contribution to the literature: (1) We confirm previous findings that the majority of the goals set by patients with upper limb spasticity are in the activity and participation category, 14,15 (2) we show that the majority of the goals set by patients with stroke and ABI who have lower limb spasticity are in the activity and participation category (see Table 3), and (3) our results extend previous findings with patients with stroke 14,15 to the population of patients with spasticity from other causes, such as spinal cord injury, MS, and CP. Individuals set activity goals to improve their physical function, which is an important domain in HRQOL.…”
Section: Discussion Activity and Participation Goals Versus Body Funcsupporting
confidence: 87%
See 3 more Smart Citations
“…Thus, our findings make a threefold contribution to the literature: (1) We confirm previous findings that the majority of the goals set by patients with upper limb spasticity are in the activity and participation category, 14,15 (2) we show that the majority of the goals set by patients with stroke and ABI who have lower limb spasticity are in the activity and participation category (see Table 3), and (3) our results extend previous findings with patients with stroke 14,15 to the population of patients with spasticity from other causes, such as spinal cord injury, MS, and CP. Individuals set activity goals to improve their physical function, which is an important domain in HRQOL.…”
Section: Discussion Activity and Participation Goals Versus Body Funcsupporting
confidence: 87%
“…A previous study of treatment of upper limb spasticity reported that 11 patients (6%) set walking and balance goals, 14 suggesting the possible impact of upper limb spasticity on walking. Our sample included patients with lower limb spasticity, which explains the much higher occurrence (30%; see Table 2) of gait-related goals in this study.…”
Section: Analysis Of Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is increasingly used as a person-centred outcome measure in research evaluations of outcome following spasticity intervention [16][17][18][19][20] , and is recommended as a method of recording patient-reported outcomes in guidelines for management of spasticity with Botulinum toxin 21 .…”
Section: Procedurementioning
confidence: 99%